ANALISIS PERSEPSI NASABAH TERHADAP PRODUK TABUNGAN MUAMALAT DAN SERVICE QUALITY BANK SYARIAH (Survey pada PT. Bank Muamalat Indonesia, Tbk Cabang Medan) - Suryani Suryani (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
This study aimed to find out customer’s perception of product savings and service quality in PT. Bank Muamalat Indonesia, in Medan. The sample of study are customers who visit the Islamic Bank. The technical sampling which used in this study are accidental sampling or convenience sampling. In other words, the technique which has been used for this study are persons who meet the researcher accidently at the location in 5 days, and the total of sample reach 50 respondents. The research instrument that used in this research are questionnaire with descriptive method for analysis. The study shows that overall from 13 questions that have been given, the response displaysthe frequency strongly disagree (0%), disagree (0.77%), neutral (11.1%), agree (40.2%), and strongly agree (48%).Quantitatively, this result indicates that the respondents generally agree with the result which has reach 90% (40.2% + 48% = 88.2%).